Pengembangan Media Pembelajaran Berbasis Teknologi Untuk Meningkatkan Hasil Belajar Siswa SD Negeri 14 Manado - Bella, Miranda Chirstina Selvy; Sumilat, Juliana Margareta; Tarusu, Deysti Trifena (Peneliti.net, 2023)
Learning media is a vehicle for transmitting learning messages and information. Learning media is designed as best as possible to improve student learning outcomes. In this era of globalization, learning media is increasingly advanced. The use of Information Technology as a learning medium has become a requirement. In order to increase the effectiveness and efficiency of learning, various creative and innovative learning models need to be developed. This research aims to meet school needs, increase interest in learning and improve student learning outcomes. SD Negeri 14 Manado. The research procedure begins with the author conducting an interview to find out about the writing of Technology-Based Learning Media Development to Improve Student Learning Outcomes at SD Negeri 14 Manado. The subjects in this research are teachers at SD Negeri 14 Manado and the research objects that will be studied are students at SD Negeri 14 Manado. The results of this media are in the form of technology-based learning, namely using power point media. This research is to see whether power point media can attract students in learning using technology.